(untitled) - Bradley, James R; Cellich, Claude (Business Expert Press, 2012)
Ebook from IG Library ; "This textbook is a concise introduction to the essential concepts and tools used in the "Lean" method of improving business processes; it constitutes a sufficient "toolkit" to enable a reader to successfully improve business processes in their workplace. While Lean was first applied in manufacturing, arguably evolving out of the Toyota Production System, it is now applied widely to service and administrative processes as well. Lean, in comparison with other business improvement processes such as Six Sigma, relies on intuitive concepts rather than complex mathematics. Thus, a short, non-technical, understandable, and engaging text can successfully convey the essential principles of Lean and empower the reader. Besides describing the concepts of Lean, plentiful examples and brief case studies illustrate the application of Lean in different contexts including manufacturing, healthcare, food service, administrative processes, distribution, and retail. Besides giving a clear idea of how to apply Lean in various contexts, the examples illustrate which Lean tools are most appropriate in the various contexts. This book focuses on "how" to do Lean in terms of what the Lean tools are and how to apply them. What this book is not is an in-depth coverage of other organizational issues associated with the successful implementation of Lean. Because these issues are important, very brief coverage is included in the Section/Chapter entitled "Other Considerations in Lean." Each subsection in this chapter would be extremely brief and would outline the relevant issues, but in no way would thoroughly discuss these topics. References would be included here for those readers who wish to pursue future study in this area.
Keywords: Supply and Operations Management